Introduction to sustainable transports - Favre, Bernard (London : ISTE Ltd ; Hoboken, NJ : John Wiley & Sons, Inc., 2014)
"Transport systems have to meet the mobility needs of people and commodities on all scales, from the local to the global level. Concerns about the energy, fumes and sound emissions produced, and about the safety, service quality, intelligence and lifecycle of the systems, etc. can all be included in a systemic approach. This approach can contribute to the development of sustainable solutions, for individual vehicles as well as for transport systems. Derived from an approach combining the social and physical sciences, these solutions result from the integration of physical objects, services and organizational processes, which involve several actors. Their harmonious organization contributes to the development of more virtuous transport systems for the future of urban and inter-urban mobility"--Provided by publisher.
Introduction -- Chapter 1. The Fundamentals of Sustainable Transport -- Chapter 2. Vehicles: An Element of the Solution for Sustainable Transport -- Chapter 3. A Systemic Approach to Transport Schemes -- Chapter 4. Can We Organize Sustainable Mobility? -- Chapter 5. Innovation Projects for Sustainable Transport Systems -- Chapter 6. Public Policies, Economics and Sustainable Transport.
Includes bibliographical references and index.
Print version record.
Keywords: Transportation -- Environmental aspects; Transportation and state; Transportation -- Planning -- Decision making; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Transportation -- Environmental aspects; Electronic books